STUDI KOMPARATIF KEMAMPUAN MENULIS TEKS NARASI ANTARA MURID PEMAIN DAN NON-PEMAIN ROBLOX KELAS IV SD IT ROBBANI KOTA BANJARBARU - Aldila Aulia; Wulida Makhtuna (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research was motivated by the widespread digital interaction of children through the Roblox gaming platform in primary school environments, which is suspected to affect students' narrative text writing skills. This study aims to determine the difference in narrative text writing ability between Roblox player and non-player students in grade IV SD IT Robbani Banjarbaru City. The research method used was a comparative quantitative approach (ex post facto). The research sample consisted of 35 students determined through a purposive sampling technique based on the results of a screening questionnaire on Roblox playing habits that met high validity and reliability criteria (r = 0.938), divided into active players (n = 15) and non-players (n = 20). Data on narrative text writing ability were collected through a narrative writing test using an assessment rubric covering five linguistic aspects (content, organization, vocabulary, language use, mechanics) validated by two experts. Data analysis used the Independent Samples t-Test parametric test with a separated variance approach (Equal Variances Not Assumed) via SPSS. Inferential test results showed a Sig. (2-tailed) value of 0.132 (p > 0.05), so H0 was accepted. Descriptively, the average score of the Roblox player group (73.00) was slightly higher than that of the non-player group (68.75). Based on the results, it can be concluded that there is no significant difference in narrative text writing ability between Roblox player and non-player students in grade IV SD IT Robbani Banjarbaru City.